Factors influencing the use of digital marketing: The case of women in the city of Arica - Viera Castillo, Daniel Omar (2023)
This article analyzes the factors influencing the use of digital marketing among women entrepreneurs in Arica. It highlights the growing relevance of digital marketing in small and medium-sized enterprises (SMEs), while also identifying barriers such as perceived costs and lack of technological knowledge. The study concludes that a strategic approach is essential to maximize the potential of digital tools and improve sales and customer relationships. Surveys and factorial analysis were conducted to identify five key factors: economic, technological, lack of knowledge, strategy, and cultural. These findings underscore the importance of promoting training and access to resources, enabling women entrepreneurs to fully harness the advantages of digital marketing in their businesses.